EFEKTIVITAS MEDIA BOOKLET TERHADAP PENINGKATAN PENGETAHUAN DAN SIKAP REMAJA TENTANG PENDEWASAAN USIA PERKAWINAN (PUP) DI DESA TG. SARANG ELANGKEC. PANAI HULU KAB. LABUHAN BATU TAHUN 2022 - KHAIRANI (EZRA SCIENCE BULLETIN, 2023)
Indonesia has the fourth largest population in the world. The target of controlling population quantity which does not meet expectations can be seen from the static total fertility rate (TFR) of 2.6 children per woman in the 2012 Indonesian Demographic and Health Survey (SDKI). More than 700 million women living today get married before reaching adulthood, namely the age of 18 years, and one third or around 250 million children are married before the age of 15. The impact of early marriage is that teenagers drop out of school which reduces the level of education and knowledge of teenagers, as well as divorce and domestic violence due to teenagers' economic and psychological unpreparedness to face the responsibilities of marriage. The National Population and Family Planning Agency (BKKBN) created a Youth Information & Counseling Center (PIK-R) program with material on Preparing for Family Life for Teenagers (PKBR) which focuses on Marriage Age Maturation (PUP). Marriage Age Maturation (PUP) contains the ideal age of marriage, family planning and aspects of family life. Booklets or pocket books are useful media for conveying health messages in the form of sheets, both writing and images, which can change a person's attitudes and behavior after being given health promotion. The aim of this research is to analyze the effectiveness of booklet media in increasing knowledge and attitudes of teenagers regarding the maturity of marriage age (PUP) in TG Village. Sarang Elang, Panai Hulu District, Labuhan Batu Regency, 2022. This research uses a quasi-experimental research method. This research shows that the booklet influences the difference in the average score of the pretest and posttest for menstrual hygiene knowledge, stating that education through the booklet increases the knowledge score at the posttest.